Ab-Interno Bleb Needling in A Failed Trabeculectomy: A Case Report: Poster Presentation - Case Report - General practitioner - Yinvill; Natan, Priscilla Christina; Rahayu, Ni Kompyang; Wetarini, Krisnhaliani (Majalah Oftalmologi Indonesia, 2023)
Introduction : Trabeculectomy remains a gold standard of glaucoma surgical management despite a steady rate of bleb failure due to conjunctival scarring. In this case, we report a case of a failed trabeculectomy managed with ab-interno bleb needling followed by antimetabolite injection of mitomycin C. Case Illustration : A 18-year-old male patient with a history of blurry vision in his right eye and vision loss in his left eye. The patient had previously undergone cataract surgery due to juvenile cataracts and developed persistent high intraocular pressure (IOP) in both of his eyes. A trabeculectomy was performed on his right eye six months prior to the examination; however, the IOP remained at 22 mmHg. Ocular examination revealed a shallow anterior chamber and flat conjunctival bleb. An ab-interno bleb needling technique was performed followed by antimetabolite injection of mitomycin C under local anesthesia in an operating theatre. Follow-up results showed a significant reduction of IOP on the first day (13.3 mmHg) and a week after surgery (18.5 mmHg), maintained by one anti-glaucoma eye drop. Discussion : Trabeculectomy filtration surgery has a high failure rate in younger patients due to a high risk of conjunctival scarring. The ab-interno needling approach with mitomycin C injection is a novel technique that can be performed and offers the advantage of increasing aqueous outflow through a direct opening of the trabecular meshwork from within the anterior chamber. Conclusion : This technique provides effective management of failed trabeculectomy to achieve intraocular pressure lowering effect and a corresponding decrease in the risk of progressive glaucomatous optic neuropathy.